Pengaruh Current Ratio, Debt to Asset Ratio dan Total Assets Turnover Terhadap Pertumbuhan Laba (Studi Pada Perusahaan Pertambangan Batubara Yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023) - Siti Mardah; Rizka Amanda Yanti; Kurniaty (PT. Karya Inovatif Nusantara, 2024)
This research aims to test and analyze the magnitude of the influence generated by CR, DAR, and TATO on profit growth in Coal Mining Companies listed on the IDX for the 2020-2023 period. The design in this study is a causal associative research type that uses documentation techniques. This study uses secondary data, namely the Company's financial statements used as samples. The subjects of this study are Coal Mining Companies listed on the IDX in the 2020-2023 period. The samples obtained were 8 companies using a purposive sampling approach with a total observation of 32 data. This research was tested using a multiple linear regression analysis approach with the test tool used by the SPSS program. The research results showed that CR and TATO did not have a significant effect on profit growth and DAR had a significant negative effect on profit growth. While simultaneously CR, DAR, and TATO did not have a significant effect on profit growth in Coal Mining Companies listed on the IDX for the 2020-2023 period.